Dissimilar regulation of glucose and lipid metabolism by leptin in two strains of gibel carp (Carassius gibelio). Issue 11 (14th June 2021) - Wu, Liyun; Li, Hongyan; Xu, Wenjie; Dong, Bo; Jin, Junyan; Han, Dong; Zhu, Xiaoming; Yang, Yunxia; Liu, Haokun; Xie, Shouqi
Abstract: Previous nutritional studies have shown that insulin regulation is different between DT and A strains of gibel carp. As leptin plays a pivotal role in the effects of insulin, we hypothesised that leptin regulation of glucose and lipid metabolism would differ between the two strains. To test our hypothesis, recombinant human leptin was injected into two strains. The results showed that leptin activated the phosphatidylinositol 3-kinase (PI3K)–protein kinase B (AKT), AMP-activated protein kinase–acetyl coenzyme A carboxylase and Janus kinase 2 (JAK2)–signal transducer and activator of transcription (STAT) signalling pathways in both strains. Hypoglycaemia induced by leptin might be due to higher glucose uptake by the liver and muscles together with enhanced glycolytic potential and reduced gluconeogenic potential. Decreased lipogenesis and up-regulated fatty acid oxidation were induced by leptin. In terms of genotype, the PI3K–AKT signalling pathway was more strongly activated by leptin in the muscle tissue of the A strain, as reflected by the heightened phosphorylation of AKT. Furthermore, glycogen content, glycolytic enzyme activity and gluconeogenic capability were higher in the A strain than the DT strain. Strain A had higher levels of fatty acid synthesis and lipolytic capacity in the liver than the DT strain, but the opposite was true in white muscle. Regarding leptin–genotype interactions, the DT strain displayed stronger regulation of glucose metabolism in the liver by leptin as compared with the A strain. Moreover, a more active JAK2–STAT signalling pathway accompanied by enhanced inhibition of fatty acid synthesis by leptin was observed in the DT strain. Overall, the regulation of glucose and lipid metabolism by leptin differed between the two strains, as expected.